'It's not about having a back-up plan; it's always being in back-up mode': Rethinking the relationship between disability and vulnerability to extreme weather. Issue 126 (November 2021) - Connon, Irena L.C.; Hall, Edward
Highlights: A relational perspective improves understanding of disability and hazard response. Interaction of agentic bodies with environments shapes vulnerability and adaptation. Social exclusion and experience of environmental adaptation influence responses. People with disabilities are as likely as others to adapt in favourable environments. Emergency responses should draw upon capabilities rather than assume dependency. Abstract: This article presents an empirically driven critique of the predominant theoretical perspective concerning the relationship between disability and vulnerability that continues to underpin much of the scholarship focusing on the human geographies of environmental hazards and disasters, as well as policies and practices of Disaster Risk Reduction. Findings from a study involving semi-structured interviews from six case study sites in the United Kingdom examining responses to prolonged electricity outages during periods of extreme weather demonstrate that the simple equating of disability with vulnerability cannot be sustained. This is because people with disabilities were no less likely than those without disabilities to be able cope and adapt to challenges imposed by extreme weather. Furthermore, in instances where people with disabilities struggled to cope, this can be seen to result from social, physical, and structural constraints, rather than the presence of impairment per se. From this, we argue that the experiences of people with disabilities can be better understood from a relational perspective, which promotes consideration of local relations, interdependencies, and networks within which people with disabilities are embedded, and through which they engage with society and place. We conclude that UK Priority Service Register (PSR) emergency response systems, like other emergency response protocols utilised in other geographic locations and which uncritically equate disability with vulnerability, need to be replaced with an approach that recognises the capabilities and agency of people with disabilities and considers how social and environmental factors interrelate to produce vulnerabilities and enhance capabilities.